Failure prediction for advanced crashworthiness of transportation vehicles. - Pickett, Anthony K.; Pyttel, Thomas; Payen, Fabrice; Lauro, Franck; Petrinic, Nikica; Werner, Heinz; Christlein, Jens (Elsevier, 2004)
During the past two decades explicit finite element crashworthiness codes have become an indispensable tool for the design of crash and passenger safety systems. These codes have proven remarkably reliable for the prediction of ductile metal structures that deform plastically; however, they are not reliable for joining systems and materials such as high strength steels, plastics and low ductility lightweight materials all of which are liable to fracture during the crash event. In order to improve crash failure prediction of materials and joining systems the CEC has recently funded a 3 year European research project dedicated to this topic. Specifically the project concerned aluminium, magnesium, high strength steels, plastics and two primary joining techniques; namely spotwelds and weldlines. Numerous new developments were undertaken including improved failure laws, adaptive meshing and element splitting to treat crack propagation. In the case of sheet stamping, investigations have also tried to account for process history effects and the metallurgical changes that occur during manufacture. This project has recently finished and this paper presents some of the key research results of the work concerning materials failure modelling.
Keywords: Crashworthiness; Material modelling; Failure modelling; Simulation